Bulk-edge coupling in the non-Abelian nu=5/2 quantum hall interferometer. - Rosenow, B; Halperin, B; Simon, S; Stern, A (2008)
Recent schemes for probing non-Abelian statistics in the quantum Hall effect are based on geometries where current-carrying quasiparticles flow along edges that encircle bulk quasiparticles, which are localized. Here we consider one such scheme, the Fabry-Perot interferometer, and analyze how its interference patterns are affected by a coupling that allows tunneling of neutral Majorana fermions between the bulk and edge. While at weak coupling this tunneling degrades the interference signal, we find that at strong coupling, the bulk quasiparticle becomes essentially absorbed by the edge and the intereference signal is fully restored. Furthermore, we find that the strength of the coupling can be tuned by the source-drain voltage.